Antibody Screening and Identification in Women of Child-bearing age in Zimbabwe. - Mandisodza, A; Musonza, R; Manase, MT (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background: Haemolytic disease of newborn is a haematological condition in which the foetal red blood cells are destroyed by the action of clinically significant alloantibodies from the mother through placental transfer leading to anaemia and jaundice. Maternal alloimmunization is well known to cause haemolytic disease of newborn. Maternal alloimmunization results in the production of antibodies by the mother after sensitization by incompatible foetal red cell antigens. The alloimmunization results from previous pregnancy, in utero haemorrhage or blood transfusion. The frequency of alloimmunization in women varies globally. The current study aimed at determining the frequency of alloimmunization in women of child-bearing ages in Zimbabwe. Methods: A cross sectional clinical and laboratory based study was conducted between January 2017 and April 2017 on women of child-bearing age attending an Antenatal Clinic at Parirenyatwa Group of Hospitals. Blood samples were collected from 268 of these women and were analyzed at the Parirenyatwa Group of Hospitals Blood Bank Laboratory. Antibody screening and identification tests were done on the sera using 2-Vial Screen Cells from the National Blood Services Zimbabwe and 9-vial Identification Panel Cells from the South African National Blood Services. Results: A total of 268 samples from women of child-bearing age attending Mbuya Nehanda Antenatal Clinic were collected and analyzed. A majority of 115 (42.9%) of the participants were in the age group of 26-30 years. The fewest were 16 (6%) and 15 (5.6%) in the 16-20 age group and over 36 years old respectively. One hundred and ninety- two (72%) and 19 (7%) of the participants had 2-3 and 4-5 previous pregnancies respectively. Seventy-three (27.2%) of the participants had previous history of obstetric complications and blood transfusion Twenty-one (28.8%) of these had been previously transfused. Miscarriages were reported in 41 (56.2%) of them and 11(15%) confirmed having had infants with neonatal jaundice. All the samples tested negative after an immediate spin technique using both reagent Screen Cells 1 and 2 following incubation at room temperature. Only 2 (0.7%) samples were strongly positive (4+) after incubation at 370C in antihuman globulin (AHG) and both were identified as anti-D. Conclusion: It can be concluded that antibody screening and identification of anti-D was significant since it is the most common alloantibody that causes haemolytic disease of the newborn (HDN). However, Rhesus HDN is largely preventable by administration of prophylactic anti-D. The prevalence of alloantibodies in women of childbearing age was within the expected range. Antibody screening and identification tests are critical to prevent HDN.